Medical Care of the Liver Transplant Patient : Total Pre-, Intra- and Post-Operative Management. - Killenberg, Paul G. (John Wiley & Sons, 2007)
Medical Care of the Liver Transplant Patient looks at monitoring and maintaining the health of organ recipients and donors, pre, during and post-operatively. There are twenty-nine chapters containing practical advice on total patient management. They are arranged into 8 sections and follow the stages of transplantation from first indication and selection of potential recipient, through to acute recovery, long-term follow-up and continued health. In this edition there are new chapters on special considerations in liver transplant patients such as viral hepatitis, alcoholic liver disease and liv.